Prevalence of Hypertension and Determination of Its Risk Factors in Rural Delhi - Jugal Kishore; Neeru Gupta; Charu Kohli; Neeta Kumar (International Journal of Hypertension)
Introduction. Hypertension is an important public health challenge in both economically developing and developed countries. It is one of the risk factors for cardiovascular mortality. Data is available on hypertension in urban population but few studies are reported in rural areas. Materials and Methods. It was a community based cross-sectional study conducted in two rural areas in Delhi among 1005 subjects selected using systematic random sampling method. WHO STEPS approach was used to collect data. Blood pressure, body mass index, and blood sugar were measured. Data analysis was done using SPSS version 16. Odds of hypertension among subjects with risk factors were calculated. p value less than 0.05 was considered significant. Results. The prevalence of hypertension was 14.1% among study subjects. Hypertension was significantly higher in individuals more than 35 years than those less than 35 years. Hypertension was significantly higher in those who take alcohol and in subjects with raised total cholesterol level but in multivariate analysis only age, education, and cholesterol levels were independently associated with hypertension. Conclusion. There is significant burden of hypertension in rural areas in Delhi. Age, education, and cholesterol levels were independent risk factors of hypertension.